Hsa_circ_0003220 Drives Chemoresistance of Human NSCLC Cells by Modulating miR-489-3p/IGF1 - Shaofeng Xia; Chenliang Wang (International Journal of Genomics)
Circular RNAs (circRNAs) have been shown to have critical roles in developing cancer and treatment resistance in an increasing body of research. The aim was to look into the functions and processes of hsa_circ_0003220 in the non-small cell lung cancer (NSCLC) chemoresistance. The NSCLC cell lines H460 and A549 were employed in present work. hsa_circ_0003220, miR-489-3p, and insulin-like growth factors (IGF1) mRNA levels were assessed with a quantitative real time polymerase chain reaction (qRT-PCR). The cisplatin, docetaxel, and paclitaxel (PTX) resistances were determined using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay, and the enzyme linked immunosorbent assay (ELISA) test measured IGF1 expression. In order to corroborate the miR-489-3p relation with hsa_circ_0003220 or IGF1, a dual-luciferase reporter method was applied. The level of hsa_circ_0003220 was raised in cells and tissues from PTX-resistant (PR) NSCLC. In PR NSCLC cells, hsa_circ_0003220 knockdown reduced chemoresistance. For the purpose of the mechanism study, hsa_circ_0003220 knockdown substantially reduced IGF1 expression via miR-489-3p sponging, reducing chemoresistance in PR NSCLC cells. By controlling the miR-489-3p/IGF1 axis, hsa_circ_0003220 knockdown helped NSCLC overcome chemoresistance, suggesting a potential circRNA-targeted therapy for the disease.